Future trends in social inequalities in obesity in England, Wales and Scotland. (11th March 2019) - Keaver, Laura; Pérez-Ferrer, Carolina; Jaccard, Abbygail; Webber, Laura
Abstract: Background: Previous studies have shown persistent or increasing socioeconomic inequalities in obesity in many European countries. The aim of this study was to project trends in social inequalities in obesity to 2035 in male and female adults (aged 16+) in the UK to ascertain if the gap is widening or narrowing. Methodology: BMI data for the UK were extracted from the Health Survey for England (2004–14), Scottish Health Survey (2008–14) and the Welsh Health Survey (2004–14), respectively. A non-linear multivariate regression model was fitted to cross-sectional risk factor data to create longitudinal projections to 2035 stratified by sex, and occupational status or education level. Results: Individuals in routine and manual jobs are projected to have the highest prevalence of obesity by 2035 and to experience the highest increases in obesity prevalence to 2035. Social inequalities based on occupation are projected to widen (except in English females). Social inequalities based on education are projected to decrease (except in Welsh females). Discussion: A population strategy of prevention focused on the structural determinants of obesity is needed to change the trajectory of obesity prevalence trends and to tackle health inequalities.